Figuring out Benjamin's 'angel of history': 'reading', Angelus Novus and sublime metaphor. Issue 6 (2nd June 2020) - Hope, Alexander
ABSTRACT: The image of the 'angel of history' forms the centrepiece of one of Walter Benjamin's most famous essays: 'On the Concept of History'. This text has a troubled exegetical history, with numerous competing interpretations attempting to explain what Benjamin really meant. Few, with the exceptions of Timothy Bahti and Sigrid Weigel, have stopped to examine the fragments' rhetorical structure or to ask what it is about 'On the Concept of History' that leads to such a proliferation of readings. This essay, rather than searching Benjamin's corpus for the ciphers to decode the fragments' meaning, instead focuses on the complex rhetorical structure of 'the angel of history'. It argues that an interplay between grammar and rhetoric induces a multiplication of possible interpretations, and indeed that this poetic density seems to involve an imperative to 'translate', both the 'original' (German or French) text and its complex relationship with the 'derived' English version, both interlinguistically and intralinguistically, as Roman Jakobson (1959) would say. It shows that this complex rhetorical structure actually performs the argument put forward in the fragments about the impossibility of historicist totalising readings of history, yet in its injunction to translate or interpret, 'bear witness to the unpresentable' (Lyotard), seems to ask that very impossible over and over again.